Formulation and Development of Ethosomal Drug Delivery System of Silymarin for Transdermal Application - almajidi, Yasir Q.; Taghi , Hassanien; Issa, Anmar A. (Iraqi Journal of Pharmaceutical Sciences, 2024)
Silymarin (SM), a natural polyphenolic flavonoid, shows antidiabetic and lipid-lowering characteristics with poor aqueous solubility and bioavailability. In the current investigation, SM-incorporated ethosomes (ETO) were designed and optimized using design expert version 8.0.7.1 to overcome these pitfalls. The SM-ETO were synthesized and subjected to determine the physical appearance, percent drug entrapment, size distribution, negative charge potential, morphology study, powder crystallinity and phase transition behaviour. Following optimization, SM-ETO were added to the carbapol-containing gel and examined for pH, rheology study, drug content and in-vitro drug release study. The results manifested that SM-ETO batches did not show phase separation at 2-8°C. The batch E8 exhibited 89.67% drug entrapment, 168 nm vesicular size, 0.367 Mw polydispersity index and -0.49 mV zeta potential. A morphological study revealed elongated spherical vesicles. X-ray diffraction study exhibit the amorphous nature of SM powder. A formulated gel revealed significant pH range of 6.94 to 7.18, respectively. It also displayed 9.187 (cp) viscosity, and 96.32 to 98.45% drug content. In vitro drug release showed 96,97,94, and 98 % SM release from gel batches. The comprehensive findings explored the enhanced solubility and bioavailability of the developed gel suggesting its potential as a nanocarrier in delivering SM for future clinical applications.